2011
DOI: 10.1007/s13402-011-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA cloning and sequencing in osteosarcoma cell lines: differential role of miR-93

Abstract: Although further studies are needed to evaluate miRNA involvement in osteosarcoma progression, miR-93 overexpression seems to play an important role in osteosarcoma cell growth and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
(49 reference statements)
2
33
3
1
Order By: Relevance
“…miR-93 is one of the miRNAs that are aberrantly expressed in tumoral tissues compared with nontumoral tissues. It has been recognized as an oncogenic miRNA that is upregulated in several types of cancer, including smallcell lung cancer [22], osteosarcoma [23], laryngeal cancer [24], hepatocellular carcinoma [13], gastric cancer [14], and ovarian cancer [25]. However, in the present study, we found that the expression level of miR-93 was significantly reduced in colon cancer compared with normal colonic mucosa.…”
Section: Discussioncontrasting
confidence: 66%
“…miR-93 is one of the miRNAs that are aberrantly expressed in tumoral tissues compared with nontumoral tissues. It has been recognized as an oncogenic miRNA that is upregulated in several types of cancer, including smallcell lung cancer [22], osteosarcoma [23], laryngeal cancer [24], hepatocellular carcinoma [13], gastric cancer [14], and ovarian cancer [25]. However, in the present study, we found that the expression level of miR-93 was significantly reduced in colon cancer compared with normal colonic mucosa.…”
Section: Discussioncontrasting
confidence: 66%
“…Our recent results demonstrated miR-93 overexpression involved in cell growth and invasion through downstream regulation of E2F1 transcription factor (11). Other studies recognized miR-34 as a direct target of p53 (12).…”
Section: Introductionsupporting
confidence: 52%
“…*P < 0.05 vs. sham group; # P < 0.05 vs. I/R + miR control group Until now, studies of miR-93 have been focused mainly on its involvement in many types of human cancers, such as glioblastoma, gastric cancer, breast carcinoma, and others. miR-93 is overexpressed in a number of types of human cancers and functions as an oncogene by targeting important cancer-related genes [25][26][27][28][29], whereas, in some types of cancers miR-93 was down-regulated and repressed proliferation paradoxically [30,31]. However, the present study is the first to investigate its role in ischemia-induced cerebral injury.…”
Section: Mir-93 Antagomir Induced Ho-1 Expression Through Nrf2mentioning
confidence: 66%